egnant women referred to Ayatollah Rouhani Hospital in Babol from 2017 to 2019 (a historical cohort study) - Mina Galshi; Zeinat Sadat Bouzari; Mojgan Naimi Rad; Shahla Yazdani; Solmaz Talebi; Afsaneh Keramat (Mashhad University of Medical Sciences, 2022)
Introduction: Drug addiction causes complications such as preterm delivery, miscarriage, intrauterine growth retardation, prenatal mortality, placental abruption, preeclampsia, premature rupture of membranes, increased cesarean section and congenital anomalies. Therefore, this study was performed aimed to investigate the prevalence of substance abuse and pregnancy outcomes. Methods: This study was conducted in two stages, initially a cross-sectional study was performed in all pregnant women referred to the maternity ward of Ayatollah Rouhani Hospital in Babol from April 2017 to March 2019. Then, a historical cohort study was conducted in which the subjects were divided into two groups: 112 addicted pregnant women and 224 non-addicted pregnant women. Data collection tool was a researcher-made checklist including: demographic information, maternal complications, and fetal-neonatal complications. Data were analyzed using SPSS software (version 21) and T-test and Chi-square test. P<0.05 was considered statistically significant. Results: The prevalence of addiction was 1.66% among 6713 pregnant women during these three years. Maternal, fetal and neonatal complications showed a significant increase among addicted mothers compared to the control group (P = 0.0001). Premature rupture of membranes in 44 women (39.28%) and preterm delivery in 32 (28.57%) were the most common complications. The chance of premature rupture of the amniotic sac was 9.09 times with a 95% confidence interval (0.058-0.211) and the chance of preterm delivery was 5 times higher with a 95% confidence interval (0.107-0.388) in addicted mothers. The chance of respiratory distress in infants born to addicted mothers was 10 times higher with a 95% confidence interval (0.058-0.227). Conclusion: Addiction during pregnancy is associated with many maternal, fetal and neonatal complications, so it is recommended that a comprehensive and specific program be performed for diagnostic, treatment and rehabilitation measures, especially to reduce the damage caused by addiction for women.